2017
DOI: 10.18388/abp.2016_1450
|View full text |Cite
|
Sign up to set email alerts
|

Association between uridin diphosphate glucuronosylotranserase 1A1 (UGT1A1) gene polymorphism and neonatal hyperbilirubinemia

Abstract: Polymorphisms of the UGT1A1 gene frequently co-exist in neonates. The presence of UGT1A1*28 polymorphism and male gender seem to predispose to neonatal hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We found a similar frequency of UGT1A1 * 60 SNPs in our population compared to wild-type. Those with this SNP are widely-known to have decreased transcriptional activity of UGT1A1 (about 60%) via an impaired gtPBREM (12, 18). This finding, however, contrasts what was reported for the Malaysian population, in which a higher frequency of UGT1A1 * 60 SNPs was observed (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found a similar frequency of UGT1A1 * 60 SNPs in our population compared to wild-type. Those with this SNP are widely-known to have decreased transcriptional activity of UGT1A1 (about 60%) via an impaired gtPBREM (12, 18). This finding, however, contrasts what was reported for the Malaysian population, in which a higher frequency of UGT1A1 * 60 SNPs was observed (11).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs of * 60 was found to co-exist with * 28 (40). It has been hypothesized that co-existence of both * 60 and * 28 SNPs would decrease the transcriptional activity of UGT1A1 by 70% (18). However, our study shows that no association could be found between individual nor multiple SNPs with developing moderate-to-severe hyperbilirubinemia compared to mild hyperbilirubinemia [OR of 1.05 (0.36–3.05) for heterozygotes and 2.4 (0.21–125.93) for homozygotes].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If more research data can be obtained, a more accurate analysis could be performed. Other variables can be used, including race, age, family history, environmental factors and lifestyle [ 29 32 ].…”
Section: Discussionmentioning
confidence: 99%